Tax Court in Indonesia: System and Principles of Rechmatigheid and Doelmatigheid Testing - Adib Brilian Muhammad; Mastur; Arum Widiastuti (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The Tax Court is defined as a judicial institution with legal authority as per Law Number 14 of 2002. However, upon closer examination, there are two judicial systems in various legal countries: the unity of jurisdiction, which is adopted by rule of law countries, where only one set of courts exists without recognizing the existence of administrative courts (including tax courts), and the duality of jurisdiction, which recognizes the existence of administrative and state administrative courts. These two systems not only differ in the organizational structure of the courts but also in legal substance and procedural law. In Indonesia, research shows that the judicial system is unique. When viewed from the perspective of the court's organizational structure, it is closer to the unity of jurisdiction system, but in terms of court principles or dispute resolution procedures, it aligns more with the duality of jurisdiction system. Therefore, the author concludes that Indonesia's judicial system is a mixed system.